Cardiometabolic Comorbidities in Patients With Psoriasis: Focusing on Risk, Biological Therapy, and Pathogenesis - Cai, Jiangluyi; Cui, Lian; Wang, Yu; Li, Ying; Zhang, Xilin; Shi, Yuling (Frontiers in Pharmacology, 2021)
Psoriasis is a chronic inflammatory disease characterized by erythematous scaly plaques, accompanied by systemic damage that leads to the development of multiple comorbidities. In particular, the association between psoriasis and cardiometabolic comorbidities, including cardiovascular diseases (CVDs), obesity, diabetes mellitus, and metabolic syndrome, has been verified in a considerable number of clinical trials. Moreover, the increased risk of cardiometabolic comorbidities positively correlates with psoriasis severity. Biologic therapy targeting inflammatory pathways or cytokines substantially improves the life quality of psoriasis patients and may affect cardiometabolic comorbidities by reducing their incidences. In this review, we focus on exploring the association between cardiometabolic comorbidities and psoriasis, and emphasize the benefits and precautions of biologic therapy in the management of psoriasis with cardiometabolic comorbidities. The pathogenic mechanisms of cardiometabolic comorbidities in psoriasis patients involve common genetic factors, lipid metabolism, insulin resistance, and shared inflammatory pathways such as tumor necrosis factor-α and interleukin-23/Th-17 pathways.